Pengaruh Creative Problem Solving (CPS) Terhadap Kemampuan Berpikir Kreatif Ditinjau dari Minat Belajar - Azizah, Zahra Noor; Santoso, Budi (Universitas Pendidikan Ganesha, 2023)
The purpose of this study was to determine the creative thinking ability and learning interest of students who took part in learning with the Creative Problem Solving (CPS) model. This study uses a quantitative and qualitative approach with a sequential explanatory design. Quantitative data analysis used t-test and qualitative data used descriptive analysis. Quantitative data were obtained through post-tests while qualitative data were collected from interviews and student learning interest questionnaires. A sample of 70 students from the entire XI class of SMAN 1 Sukahaji. Sampling was done by cluster random sampling technique. The results of the study show that the creative thinking abilities of students who follow the CPS model are better than students who take conventional learning. Furthermore, for students who have higher or lower learning interest, the application of the CPS model is better than students who take conventional learning. So, the CPS model contributes positively to students' creative thinking abilities.